Alpha‐globin gene triplication and its effect in beta‐thalassemia carrier, sickle cell trait, and healthy individual. Issue 3 (19th July 2021) - Hamid, Mohammad; keikhaei, Bijan; Galehdari, Hamid; Saberi, Alihossein; Sedaghat, Alireza; Shariati, Gholamreza; Mohammadi‐Anaei, Marziye
Abstract: The genotype and phenotype correlation between coinheritance of heterozygous beta‐thalassemia with the alpha‐globin triplication is unclear. In this study we have investigated and reviewed alpha triplication frequency in beta‐thalassemia carriers, sickle cell trait, and healthy individuals and its effect on hematological and phenotypical changes. In this study, 4005 beta‐thalassemia carriers, 455 sickle cell trait, and 2000 healthy individuals were included. Molecular characterization of beta and alpha‐thalassemia was performed. The frequencies of alpha‐globin triplication in beta‐thalassemia carriers, sickle cell trait, and healthy individuals were 67 (1.67%), 4 (0.88%), and 18 (0.9%), respectively. In total, the frequency of alpha‐triplications is approximately 89 (1.39%) in Khuzestan province, South of Iran population. We have compared the average hematological parameters of beta‐thalassemia carriers, sickle cell trait, and healthy individuals with and without alpha gene triplication. This mutation did not show any significant effect on the change of blood indices, neither in healthy individuals nor in sickle cell trait and beta‐thalassemia carriers. Therefore, there is no need to take more notice of anti 3.7 mutation in beta‐thalassemia carriers is opposed with some studies reported that the presence of excess alpha‐globin genes in beta‐thalassemia carriers can lead to the phenotype of beta‐thalassemia intermedia. Therefore, not every individual with triplicated alpha globin coinherited with beta‐thalassemia trait will have a significantly lower Hb than normal, and it is highly likely that none of them will need transfusion.